Redescription of Nemachilichthys rueppelli, a senior synonym of N. shimogensis (Teleostei: Nemacheilidae) - Keskar, Ashwini; Kumkar, Pradeep; Katwate, Unmesh; Ali, Anvar; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2015)
The hill-stream loach genus Nemachilichthys, an endemic of the Western Ghats of India, comprises two nominal species, N. rueppelli and N. shimogensis. The validity of the latter has been questioned by several authors. Here we show that there is only a marginal raw mitochondrial genetic distance (0.5% in cytochrome oxidase subunit I and 1.2% in cytochrome b) between topotypic specimens of the two nominal species. Further, although population-level morphometric variations appear in a multivariate morphometric analysis, the two nominal species are morphologically similar, with apparently no significant characters separating them. We therefore consider N. shimogensis to be a junior synonym of N. rueppelli and redescribe the latter, providing further details on population variation and distribution.